REAL ESTATE VALUATION: FORMATION AND DIRECTIONS OF IMPLEMENTATION - Kanivets, O.; Goi, V.; Viatkin, R.; Mamonov, V. (Municipal economy of cities (Technical science), 2024)
It has been proven that in modern conditions for ensuring regional development, increasing the efficiency of real estate use, which is defined as an important asset that includes a complex of structural elements, is of particular importance. An urgent issue is the provision of a complete and reliable assessment of real estate, taking into account the peculiarities of the development of regions. The formation and use of real estate is influenced by a set of factors that have a multifaceted nature. This requires the development of management solutions based on an appropriate quantitative basis. The goal of the research on the development of directions for real estate evaluation, taking into account regional aspects, has been achieved. To achieve the goal, the following tasks were solved: identifying the factors of real estate use at the regional level; definition of real estate. The definition of real estate is proposed, which, as defined, is a complex category characterized by structural components and includes land plots, objects of immovable above-ground and underground property, infrastructure structures, taking into account the space that is located next to and around the objects, and the influence of spatial, urban planning, environmental, investment factors that have long-term use and movement of which leads to a change in functional purpose. As a result of the study, a definition of real estate was proposed, which made it possible to form a theoretical and methodological basis for its assessment. Real estate valuation has a complex nature and is determined by a system of interdependent actions aimed at forming a quantitative basis for making informed decisions. For evaluation, methods and evaluation models are proposed, which forms the appropriate methodology, taking into account the influence of spatial, urban planning, environmental and investment factors. The need to transform existing approaches to real estate valuation has been established.